Insightful Discussion of Copper (I) Complexes As Promising Sensitizers for Dye-Sensitized Solar Cells - Yusuf, Anis Kharul Nada Mohd; Mustafar, Suzaliza; Kusumawati, Etty Nurlia; Borines, Leah Ma.; Juahir, Yusnita; Ali, Noorshida Mohd; Hashim, Norhayati (CENTRAL ASIA AND THE CAUCASUS, 2022)
Energy production must evolve from heavily depending on fossil fuels to renewable resources in order to cease the depletion of those resources. Solar energy development is an alternative to reduce our reliance on fossil fuels which also helps to offset global warming by reducing greenhouse gas emissions. Generally, photovoltaic (PV) cells are classified based on the generation (GEN) or category. Dye-sensitized solar cells (DSSCs) which from the third GEN are still one of the best alternatives over the silicon-devices due to its sustainability and rapid improvement in conversion efficiency. However, there are several factors hampering dependency on DSSCs such as cost and environmental concerns. Therefore, we conducted this systematic literature review based on the Scopus database to find out possible answers for those questions. To the present time, transition metal complexes based on ruthenium (Ru) are the most prevailing sensitizers. However, these noble metal-based devices are not sustainable due to the toxicity and scarcity of Ru metal. Thus, designing alternatives that transcend these drawbacks is worthwhile in the long run. In this context, copper (Cu) complexes become the prominent choice. Other than the economic benefits, Cu complexes mainly Cu(I) polypyridyl-based compounds display numerous photophysical similarities with [Ru(2,2′-bipyridine)3]2+ such as strong metal-ligand charge transfer (MLCT) absorption in the visible region and a relatively long excited- state lifetime. In summary, qualities possessed by Cu complexes are excellent as sensitizers and ideal to be the replacement for Ru complexes.